2016
DOI: 10.3390/molecules21050618
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Pd/Bacterial Cellulose Hybrid Nanofibers for Dopamine Detection

Abstract: Palladium nanoparticle-bacterial cellulose (PdBC) hybrid nanofibers were synthesized by in-situ chemical reduction method. The obtained PdBC nanofibers were characterized by a series of analytical techniques. The results revealed that Pd nanoparticles were evenly dispersed on the surfaces of BC nanofibers. Then, the as-prepared PdBC nanofibers were mixed with laccase (Lac) and Nafion to obtain mixture suspension, which was further modified on electrode surface to construct novel biosensing platform. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Furthermore, the peaks at 1162, 1107 and 1055 cm À1 can be assigned to C-C stretching vibration, skeletal vibration and ring vibration, respectively. 48 Besides, we also found four peaks at 400-1000 cm À1 (Fig. 6A).…”
Section: Morphological Characteristics Of Cellulose Produced By Komagmentioning
confidence: 62%
“…Furthermore, the peaks at 1162, 1107 and 1055 cm À1 can be assigned to C-C stretching vibration, skeletal vibration and ring vibration, respectively. 48 Besides, we also found four peaks at 400-1000 cm À1 (Fig. 6A).…”
Section: Morphological Characteristics Of Cellulose Produced By Komagmentioning
confidence: 62%
“…(Yang et al, 2009). Li, Ao, et al (2016) also reported the use of a similar in situ chemical-reduction method to develop BC-Pd biosensors.…”
Section: Biosensors Prepared From a Destroyed Bc Networkmentioning
confidence: 99%
“…In recent years, the use of nano-and biomaterials has triggered the development of novel sensing devices with high reaction rate and sensitivity. These new biosensors are being used to detect F I G U R E 8 Evaluation of the response of the BC-based biosensor prepared by Li, Ao, et al (2016) for the detection of dopamine in fluids with different interferents, including uric acid, ascorbic acid, levodopa, carbidopa and adrenaline. The good selectivity of this biosensor would make it useful to detect dopamine in human urine (reproduced from Li, Sun, et al, 2016, with…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 2 more Smart Citations